SuperDARN Radar Software Toolkit (RST) 4.3.2 - SuperDARN Data Analysis Working Group (Zenodo, 2020)
This is a patch release to include updated information for the newly added radars Dome C North (dcn) and Jiamusi (jme). As well, there is updated information for older radars South Pole Station (sps) and Dome C East (dce). Of note, the update to the hdw.dat.dce file applies to data from the start of the radar in 2013. The RST is actively developed and maintained by the SuperDARN Data Analysis Working Group (https://superdarn.github.io/dawg/).